Pemanfaatan Limbah Cangkang Kerang Dara (Andara Granosa) Sebagai Alternatif Katalisator Pada Proses Carburizing - Anshari, Satria; Ramli, Ramli; Sugiyarto, Sugiyarto (Jurnal Inovasi Teknologi Terapan, 2024)
Along with the rapid advancement of technology, the utilization of steel in the industrial world is increasing. St 42 carbon steel is a type of low alloy carbon steel, so this steel has a relatively low hardness and soft properties but has a high ductility value. It is necessary to improve its mechanical properties such as hardness. Improvement of these properties requires the park carburizing process. The purpose of this research is to determine the feasibility of turtle shell powder as a catalyst and coconut shell activated charcoal powder as a carbon source in the carburizing process of St 42 steel. The research method includes turtle shell powder with variations of 0%, 10%, 20%, and 30%, then followed by a rapid cooling process using water media. From the test results, it can be seen that the mechanical properties of the highest hardness value are found in the 20% variation of the turtle shell catalyst with a time of 9 hours experiencing an increase, inversely proportional to the hardness. impact test value with a 20% variation of the catalyst with a time of 9 hours decreased. So it can be concluded that the high hardness value will be inversely proportional to the results of the low impact test value.